1989
DOI: 10.3109/08910608909140210
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Broad Spectrum Antimicrobial Substance byLactobacillus reuteri

Abstract: Lactobacillus reuteri resides in the gastrointestinal tract of humans, swine, poultry and other animals. Resting cells of this species convert glycerol into a potent, broad-spectrum antimicrobial substance termed reuterin. Reuterin is a low molecular weight, neutral, water soluble compound, capable of inhibiting growth of species representing all bacterial genera tested thus far, including: Escherichia, Salmonella, Shigella, Proteus, Pseudomonas, Clostridium and Staphylococcus. Also affected, but to a lesser d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
149
0
13

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(164 citation statements)
references
References 8 publications
2
149
0
13
Order By: Relevance
“…We chose L reuteri because it is found naturally in humans and has been studied well with evidence to support its role as a protective organism with immunomodulation and bactericidal properties. [22][23][24][25][26] …”
Section: Resultsmentioning
confidence: 99%
“…We chose L reuteri because it is found naturally in humans and has been studied well with evidence to support its role as a protective organism with immunomodulation and bactericidal properties. [22][23][24][25][26] …”
Section: Resultsmentioning
confidence: 99%
“…This is quite different from the situation in Salmonella, where glucose and other carbohydrates strongly repress the expression of the pdu genes, preventing cofermentation of 1,2-PD (or glycerol) with simple carbohydrates (95,100). Another interesting aspect of glycerol degradation by L. reuteri is that it leads to the production of HPA (also known as reuterin), a broad-spectrum antibiotic associated with the probiotic effects of L. reuteri (152,153). Whole-genome sequence analysis revealed that genes responsible for glycerol degradation are part of the L. reuteri pdu operon (154).…”
Section: In Lactobacillus the Pdu Mcp Is Likely Used For 12-pd Andmentioning
confidence: 92%
“…A more recent one from FAO/WHO is the following: "live microorganisms that when being administered in appropriate dose, they confer a benefit of health to the receiver." Some of the health benefits which have been claimed for probiotics include the following: improvement of the normal microflora (2), prevention of infectious diseases (3,6,9,11,13,65,83) and food allergies (51,61), reduction of serum cholesterol (23,77), anticarcinogenic activity (14,18,33,35,73), stabilization of the gut mucosal barrier (79), immune adjuvant properties (15,20,24,28,36,40,77,80,92), alleviation of intestinal bowel disease symptoms (31,82), and improvement in the digestion of lactose in intolerant hosts (19,42).…”
Section: Nonpathogenic Probiotic Bacteriamentioning
confidence: 99%